COSTIMULATION SIGNALS FOR MEMORY CD8(+) T CELLS DURING VIRAL INFECTIONS - Duttagupta, Priyanka A. (2009)
Costimulation signals have been recognized as critical for optimal T cell responses and result from important interaction between receptors on the surface of T cells and their ligands on antigen presenting cells. Two families of receptors, the CD28 family and the TNFR family have been found to be major players in providing costimulation to CD8(+) T cells. Recent studies using viral infection models have highlighted the importance of CD28 costimulation signals during memory responses against viruses. PD-1 another member of the CD28 family may contribute to functional defects of helpless memory CD8(+) T cells. Members of the TNFR family such as CD27, 4-1BB, CD40, TRAIL and OX40 have also being implicated in the survival, generation, maintenance and quality of virus-specific memory CD8(+) T cells. The delivery of costimulatory molecules such as CD28, 4-1BB and OX40 can help boost the generation and function of virus-specific memory CD8(+) T cells. Taken together this suggests that the use of costimulatory molecules as adjuvants along with viral antigens in vaccines may facilitate the generation of effective antigen-specific memory CD8(+) T cell responses. Understanding the costimulatory requirements of memory CD8(+) T cells therefore may lead to improved vaccines that target anti-viral CD8(+) T cell memory.